An isoperimetric inequality involving conformal mapping - Berlinghoff, W.P.; Reid, J.D. (Proceedings of the American Mathematical Society, 1977)
This paper characterizes quasi-pure projective (q.p.p.) and quasi-pure injective (q.p.i.) p-groups, and hence characterizes all such (abelian) torsion groups. A p-group is q.p.i. if and only if it is the direct sum of a divisible group and a torsion complete group. A nonreduced p-group is q.p.p. if and only if it is the direct sum of a divisible group and a bounded group; a reduced p-group is q.p.p. if and only if it is a direct sum of cyclic groups. © 1977 American Mathematical Society.
1 citations (Crossref) [2023-10-31]
Keywords: Abelian group; Direct sum of cyclic groups; Pure exact sequence; Quasi-injective; Quasi-projective; Torsion complete; dept.mat